Obesity is associated with improved postoperative overall survival, independent of skeletal muscle mass in lung adenocarcinoma. Issue 2 (25th February 2022) - Lee, Ji Hyun; Yoon, Young Cheol; Kim, Hyun Su; Cha, Min Jae; Kim, Jae‐Hun; Kim, Kyunga; Kim, Hye Seung
Abstract: Background: Although the obesity paradox is a topic of immense interest for oncologists and epidemiologists, the mechanism underlying this unexpected benefit of obesity is poorly understood. We explored the prognostic value of obesity and its association with skeletal muscle mass. Methods: This retrospective study evaluated the data of patients who underwent surgical excision for lung adenocarcinoma between January 2011 and December 2015. Body mass index was categorized according to the criteria of the Asia‐Pacific classification. Cross‐sectional areas of the skeletal muscle, subcutaneous fat, and visceral fat were measured. Skeletal muscle mass status was defined based on the cut‐offs of skeletal muscle index (cm 2 /m 2 ), calculated as the area of skeletal muscle divided by height squared. Overall survival was estimated using the Kaplan–Meier method, and differences in survival probabilities were compared using the log‐rank test. Cox proportional hazards regression analysis was conducted to determine the association with overall survival. Results: A total of 636 patients with a median age of 61 years (interquartile range, 54.0–68.5 years; 321 men and 315 women) were included. Obese patients (body mass index ≥ 25 kg/m 2 ) had longer overall survival than non‐obese patients (mean, 110.2 months vs. 98.7 months; log‐rank P = 0.015). Under multivariable Cox proportional hazard regression analysis, obesity was associated with longer overall survival after adjusting for covariates (hazard ratio, 0.59; 95% confidence interval, 0.40–0.86; P = 0.007). The prognostic value of obesity remained and predicted favourable overall survival after additional adjusting for skeletal muscle mass status (hazard ratio, 0.57; 95% confidence interval, 0.36–0.89; P = 0.014), skeletal muscle index (hazard ratio, 0.53; 95% confidence interval, 0.33–0.84; P = 0.008), or skeletal muscle area (hazard ratio, 0.61; 95% confidence interval, 0.38–0.98; P = 0.041). No association was observed between skeletal muscle mass status and the impact of body mass index on overall survival ( P for interaction = 0.512). Conclusions: Obesity was associated with favourable overall survival, independent of skeletal muscle mass, after surgical excision of lung adenocarcinoma.